The complete mitochondrial genome of Platygaster robiniae (Hymenoptera: Platygastridae): A novel tRNA secondary structure, gene rearrangements and phylogenetic implications. (August 2022) - Huang, Lan; Sun, Hui-Quan; Li, Cheng-Jin; Zhao, Wen-Xi; Yao, Yan-Xia
Abstract: Platygaster robiniae is economically important as a highly specific parasitoid of the invasive pest Obolodiplosis robiniae which was introduced into the Euro-Asia region in the last decade. Despite being a critical and specific parasitoid of the invasive pest O. robiniae and its use as an effective biocontrol agent, the absence of sequence information from P. robiniae have limited its genetic applications for pest management in forests. Mitochondrial (mt) genomes generally contain abundant nucleotide information and thus are helpful for understanding species history. Here, we sequenced the complete mt genome of P. robiniae using next generation sequencing, and annotated 13 protein-coding, 22 tRNA, and 2 rRNA genes and a 702 bp noncoding region. Comparative analysis indicated that this mt genome has a normal A + T content and codons use, however possessed both the expected and unique rearrangements. Ten tRNAs at four gene blocks COII-ATP8, COIII-ND3, ND3-ND5 and the A + T-rich region -ND2 were rearranged, including gene shuffles, transpositions and inversions. Notably, two genes tRNA Ser(UCN) and tRNA Leu(CUN) had undergone long-range inversions, which is the first record of this rearrangement type in the superfamily Platygastroidea. The D-loops of both tRNA Ile and tRNA Leu(CUN) were absent from the tRNA secondary structure, which has not been reported from hymenopteran previously. Phylogenetic analysis based with the maximum likelihood and Bayesian methods showed that P. robiniae grouped with other species of Platygastridae, and that the superfamily Platygastridea is sister to the other Proctotrupomorpha superfamilies. Our tree strongly supports the monophyly of the five superfamilies of Proctotrupomorpha. This study discovered some unique characters of P. robiniae, and contributes to our understanding of genome rearrangements in the order Hymenoptera. Graphical abstract: The study clarified the novel mt genome and discovered some unique characters of P. robiniae, which was helpful for the understanding of the abundance rearrangements in the order Hymenoptera. Image 1 Highlights: Assemble the complete mitochondria genome of the obligate parasitoid ( Platygaster robiniae ) of Obolodiplosis robiniae . Discover some unique tRNA secondary structures. Discover some unique rearrangements of Platygaster robiniae and Platygastroidea. The abundance rearrangements in the order Hymenoptera.